THE INFLUENCE OF ORGANISATIONAL CULTURE, WORK ENVIRONMENT, AND WORK DISCIPLINE ON THE PERFORMANCE OF THE SALES DIVISION AT PT. HONDA TRIO MOTOR PALANGKARAYA - Inaarotuddujja, Inaarotuddujja; Santoso, Bowo (Yayasan Education and Social Center, 2023)
This research aims to determine the influence of organisational culture, work environment and discipline on PT employee performance. Honda Trio Motor Palangkaraya. This research is quantitative and descriptive. The population of this research is employees who work in the sales division. The sampling technique in this research used a saturated sampling method. The sample in this study consisted of 54 employees. This research shows that organisational culture, work environment and discipline can support employee performance at PT. Honda Trio Motor Palangkaraya